2022
DOI: 10.3389/fcvm.2022.963002
|View full text |Cite
|
Sign up to set email alerts
|

Effects and safety of extracorporeal membrane oxygenation in the treatment of patients with ST-segment elevation myocardial infarction and cardiogenic shock: A systematic review and meta-analysis

Abstract: BackgroundThere is a lack of large randomized controlled trials (RCTs) that comprehensively evaluate the effects of venoarterial extracorporeal membrane oxygenation (V-A ECMO)- assisted treatment of patients with ST-segment elevation myocardial infarction (STEMI) combined with Cardiogenic shock (CS). This meta-analysis aims to identify predictors of short-term mortality, and the incidence of various complications in patients with STEMI and CS treated with V-A ECMO.MethodsWe searched PubMed, Cochrane Library, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Various studies have reported different mortality rates of ECMO in patients with cardiogenic shock. Overall the results have been virtually heterogenous and the in-hospital mortality rate ranged from 40% to 60 % [22][23][24][25][26][27]. Recent clinical trials comparing the efficacy of VA-ECMO and optimal medical treatment demonstrated that using ECMO in patients with cardiogenic shock did not improve early and long-term mortality [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported different mortality rates of ECMO in patients with cardiogenic shock. Overall the results have been virtually heterogenous and the in-hospital mortality rate ranged from 40% to 60 % [22][23][24][25][26][27]. Recent clinical trials comparing the efficacy of VA-ECMO and optimal medical treatment demonstrated that using ECMO in patients with cardiogenic shock did not improve early and long-term mortality [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported different mortality rates of ECMO in patients with cardiogenic shock. Overall, the results have been virtually heterogeneous, and the in-hospital mortality rate ranged from 40% to 60% [ 22 , 23 , 24 , 25 , 26 , 27 ]. Recent clinical trials comparing the efficacy of VA-ECMO and optimal medical treatment demonstrated that using ECMO in patients with cardiogenic shock did not improve early and long-term mortality [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The IABP-SHOCK study showed that the survival of patients with MI in CS after the initial 24 hours is not associated with the cardiac index. [26] After initial shock occurred, clinical factors such as age, body mass index, lactate, anterior wall infarction, TIMI-3 flow after PCI, cardiopulmonary resuscitation time, and time from arrest to extracoporeal cardiopulmonary resiscitation may affect the clinical outcomes in MI-CS [27] ; however, the main cause of mortality during shock is multiorgan dysfunction, which is triggered by severe systemic inflammation cascade, [28] microvascular dysfunctions, and decreased perfusion to peripheral organs. [25] To prevent multiorgan dysfunction, device-related complications should be minimized during shock.…”
Section: Discussionmentioning
confidence: 99%